Managing water (in)security in Brazil - Lessons from a megacity - Claudia de Andrade Melim-McLeod (London School of Economics and Political Science (LSE), Department of International Development, 2016)
This paper discusses the 2013-2015 water crisis in S\~ao Paulo from a water governance perspective and seeks to offer an explanation for the crisis by exploring the political and administrative decisions that contributed to it. It aims to uncover the rationale behind the decision making processes that, combined with drought, led to increasing water scarcity, with a view to understanding how political economy factors impact water security in a megacity such as S\~ao Paulo. It argues that under some circumstances, elections do not promote accountability, but rather may act as an incentive to undermine it. Finally, it makes recommendations with a view to institutionalizing greater accountability, averting future crises and adapting to increased water insecurity under changing climatic conditions.
Keywords: 330; Brazil; S\~ao Paulo; Water governance; Water security; Governance; Climate Change